A Concise Overview of Bacteriophage: An Alternative to Antibiotics - Musa, Maryam Ibrahim; Muhammad, Sabiu (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This paper relates a concise overview of bacteriophage to serve as an alternative to antibiotics. Antibiotics are meant to kill or inhibit bacteria threatening humans or related biota. Bacteria are able to affect humans or biota due to ability to incite infections. The discovery of antibiotics has been considerably of important to modern medicine until recently when resistance is developing due to evolution and other prevailing forces (such as misuse, abuse, massive use, etc). Therefore, seeking alternative against infectious bacteria is imperative. Phages are viruses that kill bacteria. They are supposed candidates to kill bacteria and combat resistance to antibiotics. The phages are able to specifically invade bacteria, hijacked the host replicating machine, instruct the phage DNA replication, elicit lysis to release upcoming phages. This kills the hosting bacteria. The phages are specific, numerous, and effective. Their use should be enhanced for mankind benefits.